2011
DOI: 10.1136/oem.2010.064055
|View full text |Cite
|
Sign up to set email alerts
|

Counselling low-back-pain patients in secondary healthcare: a randomised trial addressing experienced workplace barriers and physical activity

Abstract: Current Controlled Trials ISRCTN13071157.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 39 publications
0
55
2
1
Order By: Relevance
“…The AF-test was used as an outcome measure in a RCT from 2011 that examined an intervention to assist return to work among non-surgical low-back pain patients [16]. In the 2011 study, they found that the AF-test reflected the clinical differences found by the use of questionnaire-based outcome measures [16]. However, our patient group seems to differ from their patient group in terms of poorer fitness at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AF-test was used as an outcome measure in a RCT from 2011 that examined an intervention to assist return to work among non-surgical low-back pain patients [16]. In the 2011 study, they found that the AF-test reflected the clinical differences found by the use of questionnaire-based outcome measures [16]. However, our patient group seems to differ from their patient group in terms of poorer fitness at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…A number of patients had problems coping with the AF-test, which influenced their compliance, and this might have influenced the results. The AF-test was used as an outcome measure in a RCT from 2011 that examined an intervention to assist return to work among non-surgical low-back pain patients [16]. In the 2011 study, they found that the AF-test reflected the clinical differences found by the use of questionnaire-based outcome measures [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized control trial (Jensen et al, 2011) showed a significant reduction of low back pain, when exercising three times a week for 45 minutes. The intervention was based on the underlying assumption that previous experiences with physical activity could be decisive.…”
Section: Introductionmentioning
confidence: 99%
“…The data collection was part of a randomised controlled trial [22]. As this study is a validity study the randomisation was of no interest, and all participants were included.…”
Section: Data Collectionmentioning
confidence: 99%